Public education, accountability, and yardstick competition in a federal system - Philipp Mandel; Bernd Süßmuth (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2015)
Against the backdrop of a growing national and international accountability movement in education outcomes, this study sets up a simple model of yardstick competition with incumbent-disciplining effects through voters comparing performance measures of public education both across nations and federal states. It implies a potential strategic dilemma where a single top-performance state can block reform measures that could benefit low-performance states more than would do for itself. The linchpin predictions of the model are tested by analyzing announcement effects of student achievement tests on vote and popularity (VP) functions of German national and state government incumbents.
Keywords: H75; H77; I28; 330; yardstick competition; public education; VP-functions